When the Word “No” Is Not Enough: Undesirable Romantic Attention in Lithuania During the Soviet Era - Andrijauskaitė, Ugnė Marija (History / Istorija, 2020)
Annotation. This is a publication of two oral history sources, that is, two interviews which were recorded in 2018 and 2019. These interviews tell a story about unwanted romantic attention and sexual harassment that Lithuanian women experienced in 1970s. These interviews are published with comments which show the importance of such sources for research conducted by historians, sociologists, psychologists and other researchers from humanities and/or social sciences.